Peri-operative oxygen consumption revisited: An observational study in elderly patients undergoing major abdominal surgery. Issue 1 (January 2021) - Jakobsson, Julia; Norén, Carl; Hagel, Eva; Kalman, Sigridur; Bartha, Erzsébet
Abstract : BACKGROUND: Monitoring oxygen consumption (VO2 ) is neither recommended nor included in peri-operative haemodynamic algorithms aiming at optimising oxygen delivery (DO2 ) in major abdominal surgery. Estimates of peri-operative VO2 changes are uncertain in earlier publications and have limited generalisability in the current high-risk surgical population. In a prospective non-interventional observational study in elderly patients undergoing major abdominal procedures, we investigated the change of VO2 after induction of anaesthesia and secondarily, the further changes during and after surgery in relation to DO2 and estimated oxygen extraction ratio (O2 ER) by routine monitoring. METHODS: VO2 was determined by indirect calorimetry (QuarkRMR) in 20 patients more than 65 years (ASA II to IV), scheduled for elective open upper abdominal surgery with combined epidural and general anaesthesia. Data were collected during 20-minute periods pre-operatively and after anaesthesia induction, with subsequent measurements during surgery and postoperatively. Simultaneously, DO2 was monitored using LiDCOplus. The O2 ER was estimated from arterial–central venous oxygen content calculation. Mixed models were used to analyse the peri-operative changes. RESULTS: VO2 decreased after induction of anaesthesia by a mean of 34% (95% CI, 28 to 39). After 2 h of surgery, VO2 was reduced by 24% (95% CI, 20 to 27) compared with the awake baseline measurements. Pre-operative mean DO2 was 440 (95% CI, 396 to 483) ml min −1  m −2 and decreased by a mean of 37% (95% CI, 30 to 43) during anaesthesia. The estimated O2 ER did not change intra-operatively 0.24 (95% CI, 0.21 to 0.26) but increased postoperatively to 0.31 (95% CI, 0.27 to 0.36). The changes of VO2 were parallel with changes of DO2 and O2 ER in the intra-operative period. CONCLUSION: General anaesthesia reduced VO2 by approximately a third in elderly patients undergoing major abdominal surgery. Parallel changes of intra-operative VO2 and delivery were demonstrated while oxygen extraction was low. The relevance of these changes needs further assessment in relation to outcomes and haemodynamic interventions. TRIAL REGISTRATION: Clinicaltrials.gov NCT 03355118. Abstract : Supplemental Digital Content is available in the text